Analisis Perbandingan Suara Partai Politik pada Pemilu 2019 dan 2024 DPR RI - Sahala Fransiskus marbun; Natasya Kaila Putri; Diva Nayaka Siswadi; Annisya Agustina; Iccaliona Marbun (PT. Pustaka Cendekia Publisher, 2025)
This study analyzes the comparison of the number of votes obtained by political parties in the 2019 Election and the 2024 Election for the Indonesian House of Representatives and finds out the mapping of the distribution of the number of votes for political parties in the 2019 Election and the 2024 Election for the Indonesian House of Representatives. The methods used in this study are document study analysis techniques, quantitative statistical analysis, and spatial analysis. The results of the study show significant changes in the acquisition of political party votes in Baiturrahman District, Banda Aceh City, between the 2019 Election and the 2024 Election for the Indonesian House of Representatives. In the 2019 Election, the total votes achieved reached 15,258 votes while in the 2024 Election it increased to 16,667 votes indicating an increase in participation. In the 2019 Election, the National Mandate Party (PAN) was in the top position with 3,361 votes (20.12%), followed by the Democratic Party with 2,739 votes, and the Prosperous Justice Party (PKS) with 2,655 votes. However, in the 2024 Election, there was a change in dominance, where the United Development Party (PPP) managed to win with 3,374 votes (20.24%), followed by PAN which recorded 2,768, and the Nasdem Party which experienced a significant spike to 2,716 votes..